ACUTE OTITIS MEDIA AMONG CHILDREN. MODERN APPROACH TO THE PROBLEM. VACCINE PREVENTION OPPORTUNITIES - M.V. Fedoseenko; O.V. Korneeva; M.G. Galitskaya; D.P. Polyakov; A.G. Gaivoronskaya (Union of pediatricians of Russia, 2008)
The article considers acute otitis media, which is acknowledged to be rather an urgent issue of pediatrics and particularly of infancy. The authors highlight the major aspects of the etiology and pathogenesis, diagnostics and clinical run of the given pathology. They stress difficulty of otitises treatment: antibacterial therapy justification and in the event of its application - high probability of the pathogen antibiotic resistance. Therefore, otitises vaccine prevention becomes quite perspective, which is convincingly demonstrated by the example of the conjugated vaccine against the pneumococcal infection, most often leading to the complicated otitises.Key words: acute otitis media, clinical course, diagnostics, treatment, vaccine prevention, children.